Key factors for advancing innovations to scale: Evidence from multiple country case studies of agricultural innovations - Kohl, Richard D. (Frontiers in Sustainable Food Systems, 2023)
Innovation pathways can be defined as a sequence of innovation, going to scale, and implementation at sustainable scale, where innovation is a new product, service or systems change not previously introduced in a specific context. They can take the form of new products or services, institutions, or systems change. Such pathways can play a lead role in transforming agri-food systems in low- and middle-income countries. To get us to our global goals, these pathways have to lead to impact at a scale that matches the size of the challenge. Unfortunately, while there are many proposals in the published and gray literature for integrated, transformative approaches to innovation pathways, few have yet either gone to scale or been implemented sustainably at large scale. Here we assess whether there is evidence to support these proposals about how agricultural innovation pathways should be pursued. In this paper we identify from the literature and case studies 10 potentially key factors for advancing scaling along the innovation pathway: participation, inclusion, leadership, iteration, adaptation, the specific attributes of innovation design, funding models, implementation models, systems change, and partnerships. We test these factors against a collection of innovation and scaling case studies from Bangladesh, Brazil, India, Kenya, Senegal, Uganda, and Zambia. While the cases are somewhat limited in their quantitative measures of successful implementation at scale, the qualitative evidence presented in the cases confirms both the general importance of these factors in action and that their importance varies depending on the innovation and context. While confirmation of the importance of these factors is not surprising in itself, we also demonstrate their specific design and implementation (or absence) in different contexts, how each element contributes to success at large scale, and actionable examples to be applied in practice. The paper concludes that integrating these factors will likely require changes to traditional approaches to development, innovation and scaling in agri-food systems. Specifically advancing along an innovation pathway to large scale will require a commitment of greater resources over longer time horizons. In the absence of greater overall resources, this implies focusing on fewer innovations at each phase and a greater appetite for risk and failure in individual cases, suggesting adoption of a portfolio rather than a project approach in evaluating success. This may lead to more unsuccessful individual efforts, but those will be offset by a few transformative successes which will change the lives of hundreds of millions, if not billions.